Emotions in the Hebrew Bible : a few observations on prospects and challenges - Kruger, Paul Albertus (Old Testament essays, 2015)
Although there has been significant progress in the study of emotions in the HB in recent years, a variety of matters still need attention or serious reflection. This article addresses some of these. Aspects that are focused on include : (1) the designation "emotion" and what it entails in a HB context; (2) the limitations of the original psychophysical approach; (3) the cognitive approach and the question of a dominant conceptual metaphor; (4) the social-constructionist view of emotions and the problems of translating emotional communication; and (5) some issues related to gender and emotion.,